How Tycho Brahe’s recordings in 1572 support SN 1572 as a type I(a) supernova - Hinse, Tobias C.; Dorch, Bertil F.; Occhionero, Lars V. T.; Holck, Jakob P. (Frontiers in Astronomy and Space Sciences, 2023)
The year 2022 celebrates the 450th anniversary of the discovery of the SN 1572 supernova event. A closer look at the historical development of the field of supernova astronomy reveals the scientific importance of Tycho Brahe's 1572 observations of this 'new star'. In their quest to learn more about the new type of stellar explosion and subsequent evolution, the initial protagonists in this field (Baader and Zwicky among others), gradually turned their attention to the final remnant state of these supernova events. Since the remnant object thought to be associated with the extragalactic supernova event were found to be too dim, the focus quickly was on nearby galactic events. It is at this point were Tycho Brahe's observations played an important and often overlooked role in the context of the development of stellar evolution as a scientific field. Tycho Brahe's meticulous and detailed recordings of the change in brightness of the new star allowed modern astronomers not only to classify SN 1572 as a supernova event, but also helped to pinpoint the exact astrometric location of SN 1572. These findings helped to empirically link extragalactic supernova events to nearby past supernova remnants in the Milky Way. This enabled subsequent observations allowing further characterisation.Transforming the historical recordings to a standardized photometric system also allowed the classification of SN 1572 as a type I supernova event.